2019
DOI: 10.1016/j.jrurstud.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The accidental environmentalists: Factors affecting farmers’ adoption of pro-environmental activities in England and Ontario

Abstract: Based on semi-structured interviews with 54 distinct actors in the UK and Canada, we identify a range of internal psychological orientations that are common (albeit to varying degrees) in both case study regions that, when taken together, provide a lens through which on-farm decisions relating to pro-environmental behaviours are internally analysed and subsequently operationalised. We label these orientations as Production, Business, Environmental, Lifestyle, and Farm Health. Through these orientations, we-env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 53 publications
2
35
2
Order By: Relevance
“…Nevertheless, it is difficult to disentangle whether the participatory approach has changed stakeholders' perceptions of the soil resource or whether personal motivation was the main driver towards the perception of soil functions. For instance, recent studies [73] have highlighted that stakeholders, especially farmers, may adopt pro-environmental measures for non-environmental reasons, e.g., pursuing production improvements with innovative soil management measures (e.g., the use of cover crops) or seeking personal or family health and well-being (e.g., reduced use of pesticides).…”
Section: Outcomes From Stakeholders Participatory Approachmentioning
confidence: 99%
“…Nevertheless, it is difficult to disentangle whether the participatory approach has changed stakeholders' perceptions of the soil resource or whether personal motivation was the main driver towards the perception of soil functions. For instance, recent studies [73] have highlighted that stakeholders, especially farmers, may adopt pro-environmental measures for non-environmental reasons, e.g., pursuing production improvements with innovative soil management measures (e.g., the use of cover crops) or seeking personal or family health and well-being (e.g., reduced use of pesticides).…”
Section: Outcomes From Stakeholders Participatory Approachmentioning
confidence: 99%
“…Their results further show that farmers are heterogeneous with respect to their willingness to pay for an increase in environmental benefits. Several other studies have also shown that farmers are heterogeneous with respect to their WTA payments for ecosystem services and that farmers are not behaving in a strictly profit maximizing way, e.g., [26][27][28]. If the objective is to establish mixed cropping as a cultivation method within the production portfolio of farms in the long-run, it is hence also essential to get an understanding whether farmers evaluation of the profitability levels mixed cropping needs to reach are heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan is also a large market for reusing discarded second-hand clothes, shoes, bags, and second-hand WEE items such as computers, laptops, cars, and other smart devices such as cell phones, by enhancing the lifecycle of products as well as acting as a dumping ground for developed countries [14]. There is a scarcity of studies on the informal role of WPS, most likely due to the challenging and complex nature of data collection, as WPSs attempt to preserve their social status by working inconspicuously [15]. The WPSs contributions are much needed in the least developed nations, where there are inadequate technological measures available to offer complete waste management and recycling solutions [16].…”
Section: Introductionmentioning
confidence: 99%